Meningkatkan Produktivitas Industri Kecil Menengah Kota Batam Melalui Kompetensi Inti dan Daya Saing - Yuddy Giovanna Priscilla (Jurnal Manajemen dan Bisnis Indonesia, 2018)
The purpose of this study is to measure the influence of core competencies consisting of organizational resources (shared vision, cooperation and empowerment) and organizational capabilities (knowledge management capabilities and dynamic capabilities) on the company's performance through competitive advantage in Small and Medium Industries in Batam to be able to face competition business is getting tighter due to the impact of the Asean Economic Community (AEC). The sample was taken from 105 top-level management as owners or managers of 105 Small and Medium Industries companies that have characteristics in accordance with Law No. 3 of 2014 concerning the regulation of small and medium industries using Purposive Sampling method. This study uses a comparative causal approach. The results of this study indicate that organizational resources have no significant effect on competitive advantage, but organizational resources have a significant impact on company performance. While the ability of the organization, by using the mediating role of competitive advantage has a significant effect on the performance of the company, but the ability of the organization does not have a significant direct effect on the company's performance. And for the mediation itself (competitive advantage) has a significant influence on the dependent variable (organizational performance). Keywords: Core Competence; Competitive Advantage;Organizational Resources; Organizational Capability; Organizational Performance